2019
DOI: 10.1016/j.humov.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of running speed on joint coupling coordination and its variability in recreational runners

Abstract: The purpose of this study was to examine the effect of speed on coordination and its variability in running gait using vector coding analysis. Lower extremity kinematic data were collected for thirteen recreational runners while running at three different speeds in random order: preferred speed, 15% faster and 15% lower than preferred speed. A dynamical systems approach, using vector coding and circular statistics, were used to quantify coordination and its variability for selected hip-knee and knee-ankle join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
(60 reference statements)
0
10
1
Order By: Relevance
“…It must also be acknowledged that the present study relies on investigation of joint kinematics at discrete time points (i.e., key instants). Future studies may therefore extend the current work using methodologies to investigate the continuous time series of kinematic data, such as statistical parametric mapping [40], vector coding [41] or principal component analysis [42], as well as considering other biomechanical principles not explored within this study. Additionally, differences in anthropometric data were not accounted for, where the same angular velocities and joint angles may lead to different linear velocities.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be acknowledged that the present study relies on investigation of joint kinematics at discrete time points (i.e., key instants). Future studies may therefore extend the current work using methodologies to investigate the continuous time series of kinematic data, such as statistical parametric mapping [40], vector coding [41] or principal component analysis [42], as well as considering other biomechanical principles not explored within this study. Additionally, differences in anthropometric data were not accounted for, where the same angular velocities and joint angles may lead to different linear velocities.…”
Section: Discussionmentioning
confidence: 99%
“…These coordination patterns are commonly assessed through investigating the relative motion between joints or segments of the same limb, providing a measure of intra-limb coordination (Sparrow et al, 1987) that can improve understanding of how gross movement is organised, and for gait, therefore, how the translation of the CM is controlled. Intra-limb coordination analyses have been applied to constant velocity locomotive task such as walking (Chang et al, 2008), running (Hamill et al, 1999;Floría et al, 2019), and maximal velocity sprinting (Gittoes and Wilson, 2010). Vector coding methods (Sparrow et al, 1987;Chang et al, 2008;Needham et al, 2014) output a coupling angle, which can be easily related back to angular motion, providing an intuitive applied method for assessing movement coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Assumedly, the greatest impacts on coordination during running should become apparent at times when the neuromuscular system must rapidly decelerate/accelerate the body (e.g. initial contact during stance, stance reversal, and stance to swing transition; see beginning/end of Figures 1 and 2 of Floria et al (2019)). As such, this study found that autistic adolescents demonstrated increased variability during the step-to-step transition phase, namely, loading response compared to the control group (see beginning of each figure in this study).…”
Section: Discussionmentioning
confidence: 99%